Structure and Functions of Russian Anti-Americanism: Mobilization Phase, 2012–2015. Issue 4 (4th July 2018) - Gudkov, Lev
Abstract : Post-Soviet Russia is experiencing social and cultural adjustments that are connected to longstanding Russian issues of national identity and the nation's place in the world. Public opinion research conducted in Russia shows how anti-Americanism is used as a means of defining national identity and how it has change over time.